Antigen recognition by class I-restricted T lymphocytes. - Townsend, A; Bodmer, H (1989)
The work discussed here offers a unified view of T-cell recognition and suggests that class-I and class-II molecules have a closely related function in the presentation of peptides to T lymphocytes. The epitopes recognized by class I-restricted T cells that have been defined with peptides in the 4-6 hr lysis assay have all been derived from endogenously synthesized proteins expressed by virus infected or transfected cells. Evidence is accumulating that a cytoplasmic degradation system may be involved in the generation of these epitopes. The analysis of the specificity of CTL responses with synthetic peptides has demonstrated the control of immune responses to isolated epitopes by class-I genes and the great diversity of the receptor repertoire for individual class-I-restricted epitopes.